OPTIMAL GEOPOTENTIAL MODELS OF THE EARTH’S GRAVITATIONAL FIELD FOR THE TERRITORY OF SOUTHWESTERN BULGARIA - RILA MOUNTAIN: OPTIMAL GEOPOTENTIAL MODELS OF THE EARTH’S GRAVITATIONAL FIELD FOR THE TERRITORY OF SOUTHWESTERN BULGARIA - RILA MOUNTAIN - Kirilova, Krasimira (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The subject of the study is to correctly select the most appropriate geopotential models of the Earth’s gravitational field for the study area in order to make a more reliable assessment of the accuracy of local modelling of the geoid for the territory of Rila mountain.